Perdarahan Uterus Abnormal Pada Seorang Wanita Berusia 35 Tahun : Sebuah Laporan Kasus - Perdana, Azzahra Gadis Junita; Angraini, Dian Isti (Medula, 2026)
Abnormal uterine bleeding (PUA) is a gynecological disorder that often occurs in women of reproductive age characterized by menstrual disturbances both in number and duration. The prevalence of PUA worldwide ranges from 3-30% with a higher incidence during menarche and perimenopause. In Indonesia, PUA is estimated to occur in 20% of adolescents and 50% of women aged 40-50 years. Management of PUA requires a holistic approach that includes biomedical, psychosocial and behavioral aspects. The family medicine approach is an effective strategy by considering risk factors, lifestyle, and psychosocial conditions of patients. This study used a qualitative descriptive design with a case study. Data were collected through history taking, physical examination, supporting examination, and in-depth interviews. Interventions included medical therapy, health education, lifestyle modification, and psychosocial support. Patient Mrs. F, 35 years old, had complaints of abnormal bleeding outside the menstrual phase since one month ago. Internal risk factors include lack of knowledge related to PUA, inappropriate diet, and low awareness of routine control. While the patient's external factors include lack of family knowledge about PUA, appropriate contraceptive recommendations for patients and lack of family support. After the intervention, there was an increase in patient and family knowledge, improvement in the patient's diet and physical activity, and increased family attention and support for the patient.